Quality of life in breast cancer survivors with upper extremity lymphoedema - Chachaj, Angelika; Małyszczak, Krzysztof; Lukas, Joanna; Pyszel, Krystian; Pudełko, Marek; Tarkowski, Radosław; Andrzejak, Ryszard; Szuba, Andrzej (Contemporary Oncology/Współczesna Onkologia, 2007)
Aim of study : The aim of the study was to assess quality of life in breast cancer survivors with upper extremity lymphoedema. Material and methods : 1250 women who underwent breast cancer surgery at the Lower Silesian Oncology Centre in Poland between January 1998 and December 2005 were enrolled in this mail-out survey study. The women were sent questionnaires to assess quality of life using EORTC QLQ-C30 and EORTC QLQ-BR23. The division into groups with and without lymphoedema was based on self-reports given by respondents and measurements of upper extremity circumferences taken by women who reported to have upper extremity lymphoedema. Results : The response rate was 33.47%. There were 117 women in the group with upper extremity lymphoedema and 211 women in the group without this complication. The EORTC QLQ-C30 survey showed that women with lymphoedema had lower mean values in general quality of life (QOL), in physical, emotional, cognitive, social and role functioning, increased fatigue, pain and financial problems in comparison to the group without this complication. The EORTC QLQ-BR23 data revealed altered body image, an increase in breast and arm symptoms, worse future perspectives and greater frequency of therapy side effects in women with lymphoedema. Conclusions : Upper extremity lymphoedema results in poorer quality of life in breast cancer survivors.